Sifat dan Potensi Serat Pangan pada "Gudeg Kering" - Priyanto Triwitono; Suparmo Suparmo; Zuheid Noor (agriTECH, 1999)
Gudeg is as well known traditional processed vegetable of Yogyakarta made from immature jackfruit. This research aimed to study physical and chemical properties of it's dietary fiber to elucidate the physiological effect potential in diet. Result indicatied that gudeg contained high percentages of insoluble dietary fibers (41.3 %db) in contrast to the soluble dietary fibers (14.4 %db). The water holding capacity (WHC) was 3.6 g water I g fiber, swelling 325 percent, bulk volume 1.3 ml / g fiber, and cation exchange capacity 0.08 mgreq of Na / g fiber.